2014
DOI: 10.2528/pier14080606
|View full text |Cite
|
Sign up to set email alerts
|

Breast Imaging Using Microwave Tomography With Radar-Based Tissue-Regions Estimation

Abstract: Abstract-Microwave tomography (MWT) and a radar-based region estimation technique are combined to create a novel algorithm for biomedical imaging with a focus on breast cancer detection and monitoring. The region estimation approach is used to generate a patient-specific spatial map of the breast anatomy that includes skin, adipose and fibroglandular regions, as well as their average dielectric properties. This map is incorporated as a numerical inhomogeneous background into an MWT algorithm based on the finit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 16 publications
0
37
1
Order By: Relevance
“…Nevertheless, recent studies have shown that when BMR is used in conjunction with microwave tomography, it can improve the accuracy of the diagnosis. 36 Another option that has been recently proposed is the use of contrast agents. In the last two years, the use of nontoxic compounds such as nanoparticles and free radicals have, in simulated datasets, shown promising results for enhancing the contrast between fibroglandular and malignant breast tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, recent studies have shown that when BMR is used in conjunction with microwave tomography, it can improve the accuracy of the diagnosis. 36 Another option that has been recently proposed is the use of contrast agents. In the last two years, the use of nontoxic compounds such as nanoparticles and free radicals have, in simulated datasets, shown promising results for enhancing the contrast between fibroglandular and malignant breast tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional reconstruction techniques such as filtered backpropagation (FBPP) [26] and Fourier inversion use this projection data from [0, 2π] angular coverage for accurate image recovery. Though the formulation applies to weak scatterers, it is widely used and since its introduction, a steady research focus has been maintained on this topic [27][28][29][30][31][32][33]. Present day research on DT focuses on image recovery from projection data obtained under constraints of angular coverage and/or the number of available projections.…”
Section: Diffraction Tomographymentioning
confidence: 99%
“…The scheme is applicable to microwave tomography of tissue samples. It has been of great interest in tomography of human breast to identify malignant tumours [8][9][10][11][12][13][14]. The high contrast between healthy and cancerous breast tissue provides opportunities for clearly identifying malignancies within breast tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Faster implementations for backprojections algorithms are also being intensely explored, e.g., [17]. Again, radar based methods have been combined with microwave tomography to generate higher resolutions for medical imaging [10]. Thus, any improvement in the traditional backpropagation techniques is of potential interest across multiple disciplines.…”
Section: Introductionmentioning
confidence: 99%